2016
DOI: 10.1002/app.44020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of silica on the morphology, structure, and properties of thermoplastic cassava starch/poly(vinyl alcohol) blends

Abstract: Thermoplastic cassava starch (TPS)/poly(vinyl alcohol) (PVA)/silica (SiO2) composites were prepared by a melt‐mixing method. The effects of the content and surface properties of SiO2 on the processing, mechanical properties, thermal stability, morphology, and structure of the TPS/PVA/SiO2 composites were investigated. With increasing SiO2 content, the plasticizing times of the TPS/PVA/SiO2 composites were shortened. After the SiO2 surface was treated with a silane coupling agent (KH550), the plasticizing times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…process. Few studies involving the preparation of starch/PVA blends by melt-mixing can be found in the literature (Tian et al, 2017;Liu et al, 2016), and more studies are necessary as a prior step to the manufacture of starch/PVA blends for applications such as food packaging.…”
Section: Introductionmentioning
confidence: 99%
“…process. Few studies involving the preparation of starch/PVA blends by melt-mixing can be found in the literature (Tian et al, 2017;Liu et al, 2016), and more studies are necessary as a prior step to the manufacture of starch/PVA blends for applications such as food packaging.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the fabrication of PVA based films or sheets were mainly based on solution casting methods (Briddick and others ; Hu and Wang ), which would cause low production efficiency, high energy consumption and environmental pollution. Therefore, the thermal processing of PVA has attracted great efforts of researchers and industry (Liu and others ; Guo and others ; Liu and others ; Wang and others ).…”
Section: Introductionmentioning
confidence: 99%
“…The shift of the C‐O and O‐H stretching bands to higher frequencies for the foams were attributed to the lengthening or weakening of intermolecular or intramolecular hydrogen bonds originally present in TPS 100 CNF 0.02 and TPS 100 CNF 0.02 GA x . As reported by several investigators, the extremely high diffusivity and low viscosity of scCO 2 can lead to effective plasticization of the amorphous regions of starch granules and favor water and glycerol penetration into the amorphous and/or crystalline regions of starch . This creates additional free volume in the starch and increases the mobility of the starch molecules, which is beneficial to the enhancement of the gelatinization and nucleation of the cell structure during the scCO 2 ‐assisted foaming.…”
Section: Resultsmentioning
confidence: 86%
“…As reported by several investigators, the extremely high diffusivity and low viscosity of scCO 2 can lead to effective plasticization of the amorphous regions of starch granules and favor water and glycerol penetration into the amorphous and/or crystalline regions of starch . This creates additional free volume in the starch and increases the mobility of the starch molecules, which is beneficial to the enhancement of the gelatinization and nucleation of the cell structure during the scCO 2 ‐assisted foaming. Disruption of hydrogen bonds, particularly disruption of those linking adjacent double helices within the original starch, become much easier with the aid of scCO 2 in gelatinization and foaming processes.…”
Section: Resultsmentioning
confidence: 86%